Turbulent Impinging Jets into Porous Materials - de Lemos, Marcelo J.S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This short book deals with the mathematical modeling of jets impinging porous media. It starts with a short introduction to models describing turbulences in porous media as well as turbulent heat transfer. In its main part, the book presents the heat transfer of impinging jets using a local and a non-local thermal equilibrium approach.
Impinging Jets -- Mathematical Modeling of Turbulence in Porous Media -- Turbulent Heat Transfer Modeling: One- and Two-Energy Equation Modeling -- Flow Structure of Impinging Jets -- Heat Transfer using the Local Thermal Equilibrium Approach -- Heat Transfer using the Local Non-Thermal Equilibrium Approach -- Concluding Remarks and Future Work.
Keywords: Engineering; Hydraulic engineering; Surfaces (Physics).; Engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Characterization and Evaluation of Materials; Surfaces and Interfaces, Thin Films